Enhancing the Performance of Piezoelectric Energy Harvesters Using Permanent Magnets (Journal of Engineering, 2015)
A cantilevered piezoelectric beam with a tip mass at its free end is a common energy harvester configuration. This paper introduces a new principle of designing such a harvester which increases the generated voltage without changing the natural frequency of the harvester: The attraction force between two permanent magnets is used to add stiffness to the system. This magnetic stiffening counters the effect of the tip mass on the natural frequency. Three setups incorporating piezoelectric bimorph cantilevers of the same type in different mechanical configurations are compared theoretically and experimentally to investigate the feasibility of this principle. Theoretical and experimental results show that magnetically stiffened harvesters have important advantages over conventional setups. They generate more voltage and they can be tuned across a wide range of excitation frequencies.